Business intelligence applied to ecotourism in Colombia: A case study using CRISP-DM Methodology [Inteligencia de negocios aplicada al ecoturismo en Colombia: Un caso de estudio aplicando la metodología CRISP-DM] (2019)
Tourism is a relevant economic activity for the Colombian government and given the comparative advantages that the country has, ecotourism is a prioritized focus on productive development. For tourism, the government has developed a series of information systems that allow territorial entities to make decisions and inform themselves about the activity, however these may not consider variables related to sustainable development. In this paper we propose an Information System for Nature Tourism in Colombia, where through the use of CRISP-DM, we obtain a functional prototype that allows the visualization of different variables relevant to ecotourism, in order to identify opportunities and gaps in the departments of Colombia. The prototype is socialized with experts and evidence that the system is useful to analyze the business and a series of recommendations are left for the scalability of the exercise. © 2019 AISTI.